2015
DOI: 10.1128/iai.02329-14
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Pseudomonas aeruginosa Type III Secretion System in Epithelium Traversal Depends upon Conditions of Host Susceptibility

Abstract: Pseudomonas aeruginosa is invasive or cytotoxic to host cells, depending on the type III secretion system (T3SS) effectors encoded. While the T3SS is known to be involved in disease in vivo, how it participates remains to be clarified. Here, mouse models of superficial epithelial injury (tissue paper blotting with EGTA treatment) and immunocompromise (MyD88 deficiency) were used to study the contribution of the T3SS transcriptional activator ExsA to epithelial traversal. Corneas of excised eyeballs were inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 77 publications
1
32
0
Order By: Relevance
“…The data presented here show that biofilm growth on a lens and exposure to human tear fluid can also upregulate expression of the T3SS, which can enable P. aeruginosa to traverse susceptible corneal epithelium, 25,43 an essential event in the pathogenesis of corneal infection. In the absence of lens wear, P. aeruginosa (and other microbes) cannot infect a healthy corneal surface, which has anti-adhesive properties.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The data presented here show that biofilm growth on a lens and exposure to human tear fluid can also upregulate expression of the T3SS, which can enable P. aeruginosa to traverse susceptible corneal epithelium, 25,43 an essential event in the pathogenesis of corneal infection. In the absence of lens wear, P. aeruginosa (and other microbes) cannot infect a healthy corneal surface, which has anti-adhesive properties.…”
Section: Discussionmentioning
confidence: 82%
“…Our published data show that the T3SS is involved in P. aeruginosa traversal of superificially-injured corneal epithelium in mouse models. 25,43 The net sum result on virulence of increasing T3SS expression while also reducing the number of culturable bacteria via tear fluid exposure will require further investigation. How virulence factors other than the T3SS are impacted by tear fluid also remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its pathogenic effects on cells grown in culture, ExoS causes decreased survival and greater bacterial dissemination from the lung in a mouse model of acute pneumonia (Shaver and Hauser 2004). Likewise, a functional type III secretion system was necessary for transversal of P. aeruginosa across a corneal epithelium (Sullivan et al 2015). However, until recently the mechanism behind enhanced bacterial dissemination and the cell types targeted by ExoS during pneumonia still remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MyD88, which is a critical adaptor protein for TLR‐ and IL‐1 receptor (IL‐1R)‐mediated signaling, can modulate expression of various factors including mucins, cytokines, and antimicrobial peptides. Indeed, we have demonstrated that corneal lysates from MyD88 − / − mice exhibited reduced antimicrobial activity (18). The targets modulated by MyD88 to inhibit P. aeruginosa binding to the mouse cornea, as well as how those targets relate to enhanced P. aeruginosa adhesion after tissue paper blotting, remain unknown.…”
mentioning
confidence: 99%